Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) 1. Introduction and Promalactis species list of the world - Wang, Shuxia; Hu, Sha; Li, Houhun (Zootaxa, 2015)
The current research status of the genus Promalactis Meyrick, 1908 is introduced, and a list of 243 species of this genus are provided based on a worldwide study. Two new synonyms are proposed: P. albipars Kim et Park, 2012 syn. nov. (= P. longiuncata Wang, Kendrick et Sterling, 2009), and P. akaganea Fujisawa, 2002 syn. nov. (= P. albipunctata Park et Park, 1998); four new combinations are established: P. procerella (Denis et Schiffermüller, 1775) comb. nov., P. helminthias (Meyrick, 1918) comb. nov., P. pedicata (Meyrick, 1918) comb. nov., and P. pyrotechina (Meyrick, 1935) comb. nov.; three species are transferred from Epicallima back to Promalactis: P. atrofasciella Lvovsky, 1988 comb. rev., P. subsuzukiella Lvovsky, 1985 comb. rev. and P. nadezhdae Lvovsky, 1985 comb. rev. The original citation and the synonyms are referenced. The type locality and the depository of each species are indicated in the list.